Characteristics and aqueous dye removal ability of novel biosorbents derived from acidic and alkaline one-step ball milling of hickory wood. (December 2022) - Yang, Xiaodong; Wang, Lili; Shao, Xueqin; Tong, Jin; Zhou, Jinfeng; Feng, Ying; Chen, Rui; Yang, Qiang; Han, Ye; Yang, Xizhen; Ding, Fangjun; Meng, Qingyu; et al.
Abstract: New classes of biosorbents are needed for various environment remediation applications. Thus, a facile and benign approach to synthesize porous biosorbents was developed using acidic or alkaline one-step ball milling of hickory wood biomass (AcBH and AlBH, respectively) without any external heat treatment, and their properties were compared. AcBH and AlBH were richer in O-containing functional groups, had enhanced porous structure and greater ability to remove crystal violet (CV, 476.4 mg g −1 ) and Congo red (CR, 221.8 mg g −1 ) dyes from aqueous solution, respectively, relative to hickory wood ball milled at neutral pH. Freundlich isotherm and pseudo second order kinetic models best fitted CR and CV adsorption onto biosorbents, indicating a mainly surface complexation adsorption mechanism. Further, both sorbents exhibited excellent stability and dye adsorption reusability. These results demonstrate that acidic and alkaline one-step ball milling is a facile and efficient approach for converting wood biomass into environmentally friendly biosorbents. Graphical abstract: Image 1 Highlights: Acidic and alkaline ball-milled hickory was fabricated to remove dyes. Ball-milled biosorbents presented enhanced functional groups and functionality. AcBH sorbed 476 mg g −1 of CR, much greater than that of other biosorbents. AlBH sorbed 212 mg g −1 of CV, much greater than that of other biosorbents. Dye adsorption by ball-milled biosorbents was still more than 75% after 5 desorption cycles.